2018
DOI: 10.1590/0100-5405/175591
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a standard area diagram set to evaluate bacterial blight on yellow passion fruit leaves

Abstract: Bacterial blight is one of the most important diseases of yellow passion fruit. The aim of this study was to develop and validate a set of standard area diagram (SADs) to improve the accuracy and precision of bacterial blight severity assessments on yellow passion fruit leaves. The proposed SADs, composed of illustrations of symptomatic leaves with nine severity levels (1, 2.5, 5, 10, 20, 30, 40, 50 and 62%), were evaluated by 15 raters. Accuracy, precision and reliability of the SADs were validated by quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Thus, R 2 improved for all raters using the SADs. Other studies have reported that the reliability of disease estimates also increases with the use of SADs (Bock et al., 2016; Debona et al., 2015; Dolinski, Duarte, Silva, & May‐De Mio, 2017; Monzani et al., 2018).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, R 2 improved for all raters using the SADs. Other studies have reported that the reliability of disease estimates also increases with the use of SADs (Bock et al., 2016; Debona et al., 2015; Dolinski, Duarte, Silva, & May‐De Mio, 2017; Monzani et al., 2018).…”
Section: Discussionmentioning
confidence: 96%
“…In this context, SADs are useful tools to assess the severity of plant disease because raters are able to estimate it with high accuracy and reliability. Several studies demonstrated that the use of SADs increased the accuracy, precision and reliability of the assessments of several diseases, such as blast (Rios, Debona, Duarte, & Rodrigues, 2013) and spot blotch (Domiciano, Duarte, Moreira, & Rodrigues, 2014) in wheat, Glomerella leaf spot in apple (Moreira, Duarte, & May‐De Mio, 2019), target spot in cotton (Fantin, Braga, Canteri, Dias, & Borges, 2018), frogeye leaf spot (Debona et al., 2015) and rust in soybean (Godoy, Koga, & Canteri, 2006), bacterial spot in tomato (Duan, Zhao, Wang, & Yang, 2015), rust in coffee (Capucho et al., 2011), leaf blight in eggplant (Correia et al., 2017) and bacterial blight in passion fruit (Monzani et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of blast disease of wheat leaves and bacterial blight of yellow passion was reliably assessed and validated using SADs (Figure 1). SADs improved the reliability and accuracy of disease raters in experiments of assessing the images of diseased alfala, wheat and yellow passion leaves (Bock et al, 2013;Rios et al, 2013;Monzani et al, 2018). Andrade et al (2005) on the other hand developed a set of SADs to assess leaf spots (Quambalaria eucalypti) of eucalyptus and found improvements in the precision, accuracy and (Shane et al, 1985;Bock et al, 2022).…”
Section: Standard Area Diagrams (Sads)mentioning
confidence: 99%
“…Yellow passion fruit (Passiflora edulis Sims) is a fruit crop widely cultivated and consumed in Brazil (Monzani et al, 2018). Passion fruit has vitamin A, C, and B complex, minerals such as potassium, iron, and calcium.…”
Section: Introductionmentioning
confidence: 99%